Children's reliance on shared psychological attributes to infer group membership - Köseler, Begüm. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Our social world is based on complex relationships and organizations, and sensitivity to cues that enable us to represent these relationships is crucial for navigating this complex social environment. The current research aims to shed further light on the development of social group representations and asks whether children perceive shared knowledge and shared preferences as diagnostic cues to social group membership. Although, both attributions indicate similarity between individuals, recent studies suggest that young children privilege knowledge in their group-based inferences and their social preferences. The first study was conducted with 5-year olds. Children were introduced to two novel social groups and learned about the song preference or song knowledge of one member from each group. Children were then introduced to a novel agent’s song knowledge or preference and they were asked to guess its group membership. Results showed that children did not use shared knowledge of or preference for songs between individuals to infer shared group membership. A follow up study with a similar methodology showed that 6- to 8- years old children used both cues (shared knowledge and shared preference) to infer shared group membership among individuals. These findings highlight potential differences in making predictive and diagnostic inferences and suggest that they might show different developmental trends and possibly rely on different mechanisms.
Keywords: Social groups.; School environment -- Psychological aspects.